Can the second generation succeed? - Ralf M. Mohs (Intereconomics, 1985)
The success of the newly industrializing countries of the 1970s brought with it the hope that other Third World countries would soon be able to follow a similar path to development. The conditions facing this second generation of NICs appear far more unfavourable than those which faced the first generation, however. To what extent is the latter's prescription for success still applicable?
Keywords: 330; NICs